Quantitative ultrasound assessment of bone tissue in premature newborn twins - A. Yu. Tsymbal; Yu. V. Kotlova (Patologìâ)
Multiple pregnancy is associated with a high risk premature newborn twins (PNT) birth and the formation of low bone mass. Determining the state of bone tissue (BT) after birth is important for understanding the dynamics of its changes in the PNTs’ growth.